(untitled) (Palíndromo, 2022)
The visual essay of this proposition is composed of ten photographs digitally manipulated in an embroidery software. The images present a dance between mother and daughter and their construction process unites two substantial practices in my artistic work: performative photographs with my mother and embroidery research, which now incorporates digital elements. The text discusses aspects that constitute the essay as well as some theoretical and conceptual bases that cross my artistic research. Starting from the articulation between the concepts of Escrevivência, Self-writing and Autopoiesis, I bet on the narration of the self as an erotic act and I understand eroticism as a position before the world, which concerns the aesthetic, ethical and political dimension of life in society.